Kebangkitan dan Modernisasi Dunia Islam Abad 18-20 - Cholid Lubis, Muhammad (UIN Sumatera Utara, 2025)
This journal examines the revival and modernization of the Islamic world from the 18th to the 20th centuries (1701-2000). This period was an important time in Islamic history when various regions of the Islamic world underwent social, political, economic, and intellectual changes in response to internal decline and the influence of Western colonialism. The purpose of this study is to provide an in-depth understanding and insight into the process of the revival of Muslims, the movement to renew thought, and modernization efforts in various fields such as education, government, and religion. The research method used is a qualitative approach with a literature study technique, namely examining primary and secondary literature sources relevant to the theme of Islamic revival and modernization. The results of the study show the emergence of reformist figures such as Muhammad bin Abdul Wahab, Jamaluddin al-Afghani, Muhammad Abduh, Muhammad Iqbal, and from Indonesia, KH. Ahmad Dahlan and KH. Hasyim Asy'ari. They had ideas to modernize and conclusion reform Islam to suit the challenges of the times. Furthermore, this modernization process not only strengthened Islamic identity but also paved the way for the intellectual and political revival of Muslims in the modern era.